Green Supply Chain Management Practices for Green Innovation - Agwot, Komakech Robert (Journal of Business Management and Economic Development, 2026)
Green supply chains are a central focus of environmental performance, prompting firms to rapidly adopt Green Supply Chain Management (GSCM) practices to formalize environmental priorities across sourcing, operations, logistics, and recovery. Recent empirical research on the link between GSCM and green innovation has increased but remains somewhat fragmented. This paper presents a supply chain–centered conceptual synthesis of GSCM practices to foster green innovation. It reviews both foundational and recent research, focusing on five key GSCM practices such as green purchasing, supplier collaboration, eco-design, reverse logistics, and internal environmental management, and explains how these practices enable the development of green product, process, and organizational/ managerial innovations. The review shows that green innovation is most convincingly linked to GSCM when practices form a complementary system. Specifically, upstream governance and collaboration generate environmental knowledge; eco-design translates environmental intent into innovation-ready product architectures; reverse logistics supports closed-loop learning and process renewal; and internal environmental management provides cross-functional alignment and governance to sustain innovation. This study contributes to the logistics and supply chain literature by conceptually synthesizing the operation of key GSCM practices as an integrated system to facilitate multi-dimensional green innovation along the supply chain.